2023
DOI: 10.3389/fpsyg.2023.1113143
|View full text |Cite
|
Sign up to set email alerts
|

A cross-linguistic, sound symbolic relationship between labial consonants, voiced plosives, and Pokémon friendship

Abstract: IntroductionThis paper presents a cross-linguistic study of sound symbolism, analysing a six-language corpus of all Pokémon names available as of January 2022. It tests the effects of labial consonants and voiced plosives on a Pokémon attribute known as friendship. Friendship is a mechanic in the core series of Pokémon video games that arguably reflects how friendly each Pokémon is.MethodPoisson regression is used to examine the relationship between the friendship mechanic and the number of times /p/, /b/, /d/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…The exception to this /p/ which was found to be important in the Glasgow norms model and skewed towards the female category. Cross-linguistically, including AmE, /p/ has been shown to carry sound symbolic information pertaining to friendliness or a lack of threat ( Kilpatrick et al, 2023 ) which might account for its importance in the models. An alternate interpretation is that bilabial plosives are reflective of roundness according to the maluma/takete effect.…”
Section: Resultsmentioning
confidence: 99%
“…The exception to this /p/ which was found to be important in the Glasgow norms model and skewed towards the female category. Cross-linguistically, including AmE, /p/ has been shown to carry sound symbolic information pertaining to friendliness or a lack of threat ( Kilpatrick et al, 2023 ) which might account for its importance in the models. An alternate interpretation is that bilabial plosives are reflective of roundness according to the maluma/takete effect.…”
Section: Resultsmentioning
confidence: 99%
“…Klink (2000) found that positive traits such as friendliness and prettiness are associated with front vowels in American English. Kilpatrick et al (2023) showed that cross-linguistically so-called friendship values in Pokémon are typically high in those pocket monsters with bilabial plosives in their names.…”
Section: Introductionmentioning
confidence: 99%